Introgression of Shoot Fly (Atherigona soccata L. Moench) Resistance QTLs into Elite Post-rainy Season Sorghum Varieties Using Marker Assisted Backcrossing (MABC) - Gorthy, Sunita; Narasu, Lakshmi; Gaddameedi, Anil; Sharma, Hari C.; Kotla, Anuradha; Deshpande, Santosh P.; Are, Ashok K. (Frontiers in Plant Science, 2017)
Abstract Shoot fly is a major biotic constraint in sorghum production. Management of shoot fly using insecticides is expensive and environmentally un-safe. Developing host-plant resistance (HPR) is the best method to manage shoot fly infestation. Number of component traits contribute for imparting shoot fly resistance in sorghum and molecular markers have been reported which were closely linked to QTLs controlling these component traits. In this study, three QTLs associated with shoot fly resistance were introgressed into elite cultivars Parbhani Moti (=SPV1411) and ICSB29004 using marker-assisted backcrossing (MABC). Crosses were made between recurrent parents and the QTL donors viz., J2658, J2614 and J2714. The F1s after confirmation for QTL presence were backcrossed to recurrent parents and the resultant lines after two backcrosses were selfed thrice for advancement. The foreground selection (FGS) was carried out in F1 and BCnF1 generations with 22 polymorphic markers. Forty-three evenly distributed simple sequence repeat (SSR) markers in the sorghum genome were used in background selection to identify plants with higher recurrent parent genome recovery. By using two backcrosses and four rounds of selfing, six BC2F4 progenies were selected for ICSB29004× J2658, five BC2F4 progenies were selected for ICSB29004 × J2714 and six BC2F4 progenies were selected for Parbhani Moti × J2614 crosses. Phenotyping of these lines led to the identification of two resistant lines for each QTL region present on chromosome SBI-01, SBI-07 and SBI-10 in ICSB 29004 and Parbhani Moti. All the introgression lines showed better shoot fly resistance than the recurrent parents and their agronomic performance was the same or better than the recurrent parents. Further, the introgression lines had medium plant height, desirable maturity with high yield potential which makes them better candidates for commercialization. In the present study, MABC has successfully improved the shoot fly resistance in sorghum without a yield penalty. This is the first report on the use of MABC for improving shoot fly resistance in Post-Rainy season sorghum.